TOTAL PLATE COUNTS OF BACTERIA IN THE FECES OF STARTER AND FINISHER AGE BROILERS IN BADUNG REGENCY - Matilde Fatima Correia; I Ketut Suada; Tjokorda Sari Nindhia (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Broiler chickens are a superior breed resulting from crossbreeding different chicken breeds with high productivity, especially in meat production. Chicken feces are the final product of the digestion process of feed and water consumed by livestock, in both liquid and solid forms. This study aims to determine the total plate count (TPC) of bacteria present in the feces of broiler chickens at the starter and finisher stages in Badung Regency. This research is an observational study using purposive stratified random sampling with a quantitative analysis approach. A total of 3 grams of broiler chicken feces were collected from each farm in Mengwi, Abiansemal, and Petang Districts. The total plate count of bacteria was determined using the culture method on Nutrient Agar media. The identified bacterial colonies had characteristics such as a clear white color, round shape, and glossy appearance. Data analysis was performed using variance analysis (ANOVA), and if significant differences were found (P<0.05), Duncan’s Multiple Range Test was conducted. Before analysis, the TPC data were transformed into log Y. The results showed that the TPC (log Y) in Mengwi District was 8.0608 CFU/g at 1-21 days of age and 7.6132 CFU/g at 22-35 days of age. In Abiansemal District, the values were 8.0928 CFU/g at 1-21 days and 7.7941 CFU/g at 22-35 days, while in Petang District, the values were 8.1476 CFU/g at 1-21 days and 7.9565 CFU/g at 22-35 days. Overall, the highest TPC was found in Petang District, followed by Abiansemal and Mengwi. It can be concluded that there is a significant difference (P<0.05) in the total plate count of bacteria in broiler chicken feces across the three districts based on the age groups of 1-21 days and 22-35 days. Further research is needed on broiler farm waste management following Indonesian National Standards (SNI) .